2010
DOI: 10.1111/j.1365-2656.2010.01704.x
|View full text |Cite
|
Sign up to set email alerts
|

Match or mismatch: the influence of phenology on size‐dependent life history and divergence in population structure

Abstract: Summary1. In gape-limited predators, body size asymmetries determine the outcome of predator-prey interactions. Due to ontogenetic changes in body size, the intensity of intra-and interspecific interactions may change rapidly between the match situation of a predator-prey system and the mismatch situation in which competition, including competition with the prey, dominates. 2. Based on a physiologically structured population model using the European perch (Perca fluviatilis), analysis was performed on how prey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(41 citation statements)
references
References 57 publications
(142 reference statements)
1
40
0
Order By: Relevance
“…With increasing size and, thus, decreasing gape size limitations, the potential to use more diverse prey items regularly increases, and consequently, competition on food resources may be reduced (Beeck et al, 2002;De Roos et al, 2003;Borcherding et al, 2010). Similar as for the juveniles, the adults of P. kessleri had a significantly higher ISF than N. melanostomus while co-occurring in the riprap structures (Fig.…”
Section: Seasonal Aspects Of Feedingmentioning
confidence: 71%
“…With increasing size and, thus, decreasing gape size limitations, the potential to use more diverse prey items regularly increases, and consequently, competition on food resources may be reduced (Beeck et al, 2002;De Roos et al, 2003;Borcherding et al, 2010). Similar as for the juveniles, the adults of P. kessleri had a significantly higher ISF than N. melanostomus while co-occurring in the riprap structures (Fig.…”
Section: Seasonal Aspects Of Feedingmentioning
confidence: 71%
“…In fall spawners, this can stem from factors such as exposure to higher, harmful temperatures in fall (Casselman 2002) and premature hatching in spring that leads to a mismatch between initiation of larval feeding and the start of the spring production pulse (Pörtner and Peck 2010). De-synchronization of matched feeding phenologies (and vice versa) among younger and older fish can also change inter-specific interactions from predation to competition (and vice versa) with significant consequences for both growth and survival (Borcherding et al 2010). In spring river spawners, de-sychronization of the typical flood cycle from the fixed photoperiod cycle may have similar effects on species that use the timing of the first spring flood as the proximate cue to initiate spawning migrations.…”
Section: Sensitivity To Climate Change Is Shaped By Winter Strategiesmentioning
confidence: 99%
“…Many studies on the development of bimodality either identified an initial size difference [12] or a single discrete accelerated growth period of one part of the population [1,13] as the origin of within-cohort size variation. However, in a population with a bimodal size distribution, there are often also some individuals with intermediate size.…”
Section: Introductionmentioning
confidence: 99%
“…Such a static view may, however, neglect dynamic processes that allow some individuals within the cohort to shift from the smaller to the larger fraction, beyond initial size differences or one-time growth accelerations. One consequence of a broad size-distribution (like bimodality) within an age-cohort can be mainly attributed to differential resource use and the consequential reduction of intra-cohort competition [13,14,15]. One can hypothesize the existence of medium-sized individuals that consume alternative food resources that are not used by the bulk of small or large individuals (e.g., feeding on macroinvertebrates if the majority of the conspecifics prey zooplankton).…”
Section: Introductionmentioning
confidence: 99%